2015
DOI: 10.1007/s11442-015-1168-9
|View full text |Cite
|
Sign up to set email alerts
|

Aridity trend and response to vegetation restoration in the loess hilly region of northern Shaanxi Province

Abstract: Detecting variation trend in dry-wet conditions can provide information for developing strategic measures to mitigate the impacts of global warming, particularly in dry regions. Taking the hilly region of northern Shaanxi on the Loess Plateau as a case area, this study analyzed the trend of aridity variation during 1981-2012, and explored the effect of vegetation restoration promoted by the Grain-for-Green (GFG) program implemented in 1999. The results indicated that the aridity in the region was non-significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Changes in the timing and size of precipitation events may reduce the locale scale temperature due to increased cloud cover reducing solar radiation [57]. Other studies also showed an increasing trend of precipitation and a stable trend of temperature for the Loess Plateau during 2000-2012 [58][59][60], which was consistent with our findings. The EVI had a strong and significant increasing linear trend across all seasons in the study area during 2000-2015.…”
Section: Observed Trends Of Vegetation Growth and Climatic Factorssupporting
confidence: 92%
“…Changes in the timing and size of precipitation events may reduce the locale scale temperature due to increased cloud cover reducing solar radiation [57]. Other studies also showed an increasing trend of precipitation and a stable trend of temperature for the Loess Plateau during 2000-2012 [58][59][60], which was consistent with our findings. The EVI had a strong and significant increasing linear trend across all seasons in the study area during 2000-2015.…”
Section: Observed Trends Of Vegetation Growth and Climatic Factorssupporting
confidence: 92%
“…To alleviate the severe land degradation in this region, the Chinese Government implemented the Grain‐for‐Green (GFG) Programme in 1999, which mandated (by grain and financial subsidies to the involved farmers) converting steeply sloping croplands to forestlands or grasslands as well as afforestation. Stimulated by this ecological restoration programme, the land use has changed significantly (Li & Lu, ), providing an excellent opportunity to study the consequent impacts of these types of change on the hydrologic cycle and soil erosion, which will contribute to the understanding of the effectiveness of revegetation in reducing water and soil losses in semi‐arid areas. Previously, two studies have estimated the changes in erosion in the Loess Plateau between 2000 and 2008 with the Universal Soil Loss Equation (USLE; Fu et al, ) and between 2000 and 2010 with the revised USLE (Sun, Shao, Liu, & Zhai, ), both of which found that the soil erosion was obviously reduced, mainly as a result of land‐use change.…”
Section: Introductionmentioning
confidence: 99%
“…However, the climate data shows parallel trends of increasing precipitation and stable temperatures from 2000 to 2012, suggesting a trend of decreasing aridity in this region [32,33]. Generally, the body of knowledge relating to increasing aridity deems that an arid climate impedes vegetation growth.…”
Section: Introductionmentioning
confidence: 99%